Increased Expression of the Calcium-Activated Chloride Channel in Hclca1 in Airways of Patients with Obstructive Chronic Bronchitis. Issue 3 (3rd April 2005) - Hauber, Hans-Peter; Bergeron, Celine; Tsicopoulos, Anne; Wallaert, Benoit; Olivenstein, Ron; Holroyd, Kenneth J; Levitt, Roy C; Hamid, Qutayba
Abstract : BACKGROUND: Interleukin (IL)-9 and its effect on enhancing the human calcium-activated chloride channel 1 (hCLCA1) expression have been shown to induce mucin production. Increased expression of hCLCA1 may, in turn, contribute to mucus overproduction in chronic obstructive pulmonary disease (COPD) with a chronic bronchitis (CB) phenotype. OBJECTIVE: To determine the expression of IL-9, IL-9 receptor (IL-9R), hCLCA1 and mucoglycoconjugates in COPD. METHODS: Bronchial biopsies were obtained from six patients with obstructive CB and six healthy control subjects. IL-9, IL-9R and hCLCA1 expression were detected using immunohistochemistry. Additionally, in situ hybridization was performed to determine the expression of hCLCA1 messenger RNA. Mucin production was assessed using periodic acid-Schiff staining. RESULTS: There was a significantly higher number of IL-9 immunoreactive cells in the submucosa of patients with COPD than that of healthy control subjects (P<0.05). Also, a significant increase in the expression of IL-9R, hCLCA1 (protein and messenger RNA) and mucin (periodic acid-Schiff-positive cells) was noted in the bronchial epithelium of patients with COPD compared the control subjects (P<0.05). CONCLUSIONS: Increased expression of IL-9, IL-9R and hCLCA1 in the bronchial mucosa of patients with obstructive CB suggests that mucus overproduction in this disease may be, at least in part, due to hCLCA1.